Implementation of Promotion Mix in Increasing Visits at Kalya Hotel Yogyakarta - Dyaloka Puspita Ningrum; Frima Bowo; Rebaudhy Mahardhika Pamungkas (POPULIKA, 2025)
The increasingly massive business dynamism in the hotel industry means business competition is no longer avoidable. The emergence of new hotels with a more modern feel, quality services, and very attractive promotional activities in various marketing media is a series of activities that Kalya Hotel Yogyakarta needs attention to. This research aims to analyze the application of the Kotler and Armstrong Promotion Mix with five components, namely Advertising, Sales Promotion, Public Relations, Personal Sales, and Direct Marketing, in increasing sales and maintaining the trust of guests/consumers. By using descriptive qualitative methods with purposive techniques in determining research informants, the results in the field show that the Promotion Mix at Kalya Hotel Yogyakarta has been used as a whole, although it is still not optimal. The use of social media, giving shopping vouchers and discounts, and other efforts are starting to be adjusted based on current developments. In the future, Kalya Hotel Yogyakarta will also have to increase the capacity of human resources/employees at that place and choose and consider other modern media that can further maximize targeted promotional activities. Keywords: Promotion Mix; Visits; Kalya Hotel Yogyakarta.